Perfluoropolyalkylether Maleimides for Protection From Oxygen Inhibition and Surface Modification of Photoinitiator-Free UV-Cured Polymers - Bonneaud, Céline; Burgess, Julia; Vitale, Alessandra; Trusiano, Giuseppe; Joly-Duhamel, Christine; Friesen, Chadron M.; Bongiovanni, Roberta (Frontiers in Materials, 2020)
Maleimides are attractive systems for photopolymerize for two major reasons: (1) they follow a radical mechanism without requiring a photoinitiator and (2) their rate of polymerization corresponds similarly to acrylates, which are commonplace in the industry. In this work, bismaleimide polypropylene oxide was cured under UV light forming thin films. Their surface properties were modified by copolymerization them with fluorinated comonomers. To this goal, perfluoropolyalkylethers (PFPAEs) with maleimide groups were synthesized, varying their chain structure, their functionality degree and consequently their intrinsic viscosity. These PFPPAE comonomers were highlighted to segregate at the surface, assuring omniphobic properties and acting as a protective layer against oxygen inhibition. These phenomenon were observed even when added at a concentration ≤5% w/w with respect to the main polypropylene oxide monomer. XPS analyses confirmed the segregation of the fluorine atoms at the surface during the UV-curing process of the coatings.